OPTIMIZATION OF CALIPER BRACKET DESIGN AS AN EFFORT TO IMPROVE FUEL EFFICIENCY - Wilujeng, Auliana Diah; Fatah, Misbakhul; Ridwan, Muhammad (Jurnal Rekayasa Mesin, 2025)
Ragapadmi's automobile was modified by the Sevta team so that it could compete in the KMHE race. To increase fuel efficiency, the car's materials and design were altered. In order to decrease excessive friction in the brake system, the caliper bracket needed to be adjusted. Lightweight and simple materials also needed to be used when doing repairs. Therefore, to minimize caliper friction when not braking, a perfect bracket is required. Three different caliper bracket designs were created to create a suitable (strong, light, and precise) bracket that can resist the 569.43 N braking force of the Ragapadmi automobile. Utilizing CAD and CAM tools to simulate strength, the strength of the brackets and materials is tested by creating a CNC toolpath program. The aluminium 6061 material used to make the calliper bracket is robust, lightweight, and precise. Following strength modelling, model 3 provides a mass of 0.099567 kg and a deflection value of 0.084 mm. The caliper bracket was machined in 174.86 minutes using a CNC milling machine, and its roughness value is 0.432µm, or N5 roughness class.